Ecotourism in the Traditional Village of Nagari Sijunjung: A Hidden Paradise in the Land of Minang - Khasanah, Lailatul; Eka Asih Febriani; Azmi Fitrisia; Erianjoni; Samadi (Sumatra Journal of Disaster, Geography and Geography Education, 2026)
The traditional village of Nagari Sijunjung in West Sumatra is one of the ecotourism destinations that combines natural beauty with the rich culture of Minangkabau. This study aims to identify the potential for ecotourism, cultural preservation, and the social and economic impacts on the local community. Using a descriptive qualitative approach, data was collected through observation, interviews, and documentation studies. The results of the study show that this area has high appeal as a cultural and environmental tourism destination.